Enhancement of Radiative Cooling Effect by Bioinspired Hollow-core Triangular Structures. Issue 1 (1st January 2022) - Li, Ke; Zhang, Tianshun; Pan, Lei; Zhang, Xinyuan; Xu, Xiudong; Dou, Shuliang; Li, Yao; Zhan, Yaohui
Abstract: Inspired by the curiousness that what happens if the silver ant's hair is designed to be hollow-core rather than solid-core while maintaining its triangular shape, the thermoregulatory response of both the solid- and hollow-core schemes are investigated comprehensively in a photothermal viewpoint. Optical responses, power balances, and field distributions collectively show that the hollow-core system has many advantages over the solid-core system in terms of selective reflection, omnidirectional absorption capability, and overall cooling performance. The investigation sheds more light on the physics in the hollow-core structures and suggests an alternative biomimetic scheme for thermal management.